Hydrogen-rich syngas production from biomass in a steam microwave-induced plasma gasification reactor. (October 2021) - Vecten, Simon; Wilkinson, Michael; Bimbo, Nuno; Dawson, Richard; Herbert, Ben M.J.
Graphical abstract: Highlights: Biomass converted to combustible gas in a steam microwave-induced plasma reactor. Complete biomass conversion and energy recovery into syngas is achieved. Generated syngas rich in hydrogen with concentration exceeding 60% by volume. Generated syngas with low inert dilution and calorific value ranging 10.5–12 MJ/Nm 3. Abstract: Substitution of fossil fuels by sustainable practices must be rapidly implemented to mitigate the impacts of climate change. The conversion of biomass into combustible gas is investigated in a microwave-induced plasma reactor using pure steam as the plasma working gas for the first time. The optimum results are achieved at the highest forward microwave power of 6 kW with biomass carbon conversion efficiency over 98% and complete biomass energy recovery in syngas. Unreacted steam is simply condensed out, leading to the production of a syngas with low inert dilution and high calorific value in the range 10.5–12 MJ/Nm 3 . The syngas produced is rich in hydrogen, exceeding 60% by volume. The proposed process could aid in the transition to a carbon neutral economy as it has the potential to efficiently convert biomass to syngas that can be used for the sustainable generation of fuels, chemicals and energy.